Circulating tumor cells in uveal melanoma. (January 2011) - Torres, Virginia; Triozzi, Pierre; Eng, Charis; Tubbs, Raymond; Schoenfiled, Lynn; Crabb, John W; Saunthararajah, Yogen; Singh, Arun D
Despite advances in the diagnosis and local tumor control, the overall mortality rate for uveal melanoma remains high because of the development of metastatic disease. The clinical and histopathological systems currently being used to classify patients are not sufficiently accurate to predict metastasis. Tumor genotyping has demonstrated significant promise but obtaining tumor tissue can be problematic. Furthermore, assessment of tumor tissue does not indicate whether tumor cells have actually been shed and cannot indicate whether treatment is reducing metastasis. The detection of circulating tumor cells in blood has been shown to be a prognostic biomarker that can be used to monitor the effectiveness of therapy in patients with metastatic carcinoma. Uveal melanoma disseminates hematogenously, and the detection of circulating melanoma cells may potentially be useful for diagnosis, risk stratification, and the monitoring of disease progression and treatment efficacy. PCR-based and immunomagnetic cell isolation techniques, derived from studies in patients with cutaneous melanoma, have been tested. For various biological and technical reasons, they have not demonstrated the accuracy and reproducibility required for an effective prognostic assay in patients with uveal melanoma. Assessments have been confounded by false positives and negatives and thus, correlations between circulating melanoma cells and survival have not yet been established. Circulating melanoma cell detection is a valuable tool for investigating metastasis in uveal melanoma and also has the potential to become a standard part of uveal melanoma management. However, more research on the biology of uveal melanoma as well as improvements upon the current technologies are needed.